HE ANALYSIS ON STUDENTS ERROR IN USING SIMPLE PRESENT TENSE AT SMP N 3 KARANGANYAR - Febriana Sabela (English Research Journal : Journal of Education, Language, Literature, Arts and Culture, 2021)
This research was entitled “The analysis on Students Errors in using Simple Present Tense at SMP N 3 Karanganyar”. The objectives of this research were to identify type of error and the dominant error made by students in using Simple Present Tense at SMP N 3 Karanganyar. This research was a qualitative research with the type of error analysis. There were 21 students involved in this research from class VIII A of SMP N 3 Karanganyar. To collect the data the researcher held a writing test of Descriptive Text in order to get the data from the students. After collecting the data, the researcher analyzed the data using data collection, data reduction, data display and drawing conclusion. The result of this research showed that there were several errors that students made in using simple present tense. There are classified into omission, addition, misformation, misordering. The errors of omission was 14 errors. The errors of Addition was 3 erros. The error that frequently made by students was misformation which was done for 43 errors. The errors of misoerdering was 1 erros.   Keywords: Error Analysis, Simple Present Tense, Misformation